Development of Synergetic Approach in Sociology and Social Forecasting - Brazevich, Svyatoslav (Journal of Sociology: Bulletin of Yerevan University, 2012)
In the article S. Brazevich represents the development of synergetic approach in sociology and social forecasting. The author describes the real model wherephilosophical representations about parity of necessity and accident collide. His ideas have been based on ideas of the leading scientists in the given area, and now professor Brazevich puts forward the idea that development of synergetic approach and political dynamics can show a new vision of unity of the world.